2016
DOI: 10.1177/0165025415620059
|View full text |Cite
|
Sign up to set email alerts
|

Associations between mother–child relationship quality and adolescent adjustment

Abstract: This study used a genetically controlled design to examine the direction and the magnitude of effects in the over–time associations between perceived relationship quality with mothers and adolescent maladjustment (i.e., depressive symptoms and delinquency). A total of 163 monozygotic (MZ) twins pairs (85 female pairs, 78 male pairs) completed questionnaires at ages 13 and 14. Non–genetically controlled path analyses models (in which one member of each twin dyad was randomly selected for analyses) were compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Focusing on positive parenting, factors such as parental knowledge of offspring whereabouts, good parent–child relationship quality, positive reinforcement, and warm parenting were associated with fewer externalising problems 50 52 , 59 , 64 , whereas there were no associations between parental positive reinforcement and ADHD symptoms 52 , or maternal support and offspring delinquent behaviour 65 . Investigation of possible gene-environmental correlation between parenting and offspring externalising behaviours in adoption samples found no passive or evocative rGE effects in the associations between parental knowledge and offspring externalising behaviours 59 , whereas one study reported an evocative rGE showing that parental hostility was evoked by genetically influenced offspring behaviour 61 , and another reported child-to-parent effects on maternal support and negativity 65 . As well as highlighting the bidirectionality of parent–offspring associations, these studies show that associations between parenting and offspring outcomes vary by phenotype and no single explanation fits all parenting–offspring associations.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Focusing on positive parenting, factors such as parental knowledge of offspring whereabouts, good parent–child relationship quality, positive reinforcement, and warm parenting were associated with fewer externalising problems 50 52 , 59 , 64 , whereas there were no associations between parental positive reinforcement and ADHD symptoms 52 , or maternal support and offspring delinquent behaviour 65 . Investigation of possible gene-environmental correlation between parenting and offspring externalising behaviours in adoption samples found no passive or evocative rGE effects in the associations between parental knowledge and offspring externalising behaviours 59 , whereas one study reported an evocative rGE showing that parental hostility was evoked by genetically influenced offspring behaviour 61 , and another reported child-to-parent effects on maternal support and negativity 65 . As well as highlighting the bidirectionality of parent–offspring associations, these studies show that associations between parenting and offspring outcomes vary by phenotype and no single explanation fits all parenting–offspring associations.…”
Section: Resultsmentioning
confidence: 95%
“…These findings are compatible with previous literature which shows a moderate impact of offspring’s genetically influenced behaviours on parenting factors 118 , 119 . In instances where evocative rGE effects were not observed, child-to-parent effects were sometimes still present 19 , 28 , 30 , 32 , 36 , 65 . These findings highlight the bidirectional and dynamic nature of parent–offspring associations, with child-to-parent effects, as well as parent-to-child effects, and also show the importance of cross-lagged models in modelling parent–offspring associations over time.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, although studies have applied the Family Stress Model to predict substance use in adolescence, most have used cross-sectional data which limits temporal ordering of causal influences (Conger et al, 1991). Moreover, many studies have merged parenting of mothers and fathers (Piko & Balázs, 2012), have solely focused on the mother-child relationship (Guimond et al, 2016), or have not taken parent alcohol use into account (Conger et al, 1991). Finally, it is important to investigate the continuity of alcohol use from adolescence to emerging adulthood (Varlinskaya, Truxell, & Spear, 2014) in rural samples as research indicates that rural youth may be at higher risk for alcohol use disorders than those from urban settings (Gale, Lenardson, Lambert, & Hartley, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Differences between friends in internalizing behaviors seem to be a disruptive force. As suggested by interpersonal models, anxious and depressed individuals create an aversive and stressful social environment (Rudolph et al, 2000), in which the better adjusted partner may initially respond to the less well-adjusted friend by increasing social support to levels that eventually prove unsustainable (Coyne, 1976a;Guimond et al, 2016). When supportive interactions are scaled back, the adolescent with greater internalizing difficulties may react in ways that both worsens symptoms and alienates the over extended friend.…”
Section: Submissivenessmentioning
confidence: 99%